IMPORTANCE PERFORMANCE ANALYSIS AT ABU SAAD GUMUKMAS CLINIC - Ikfani, Firsa Zerlinda Azza; Setianingsih, Wahyu Eko; Nursaidah, Nursaidah (Jurnal Comparative: Ekonomi dan Bisnis, 2025)
This study was conducted with the aim of measuring the level of customer satisfaction with the quality of service at the Abu Saad Gumukmas Clinic, Jember. The dimensions used to measure service quality are tangible evidence, reliability, responsiveness, assurance, empathy. The population used in this study were outpatients and inpatients at the Abu Saad Gumukmas Clinic, Jember. The sampling method used was purposive sampling using the Slovin formula of 100 respondents. Data collection techniques were carried out through the distribution of questionnaires and documentation. The data analysis method used was quantitative descriptive analysis, validity test, reliability test, Importance Performance Analysis which contained a Cartesian diagram to determine the level of performance and importance. The results of this study indicate that the level of suitability of respondents from all attributes of patient satisfaction at the Abu Saad Gumukmas Clinic, Jember to service quality was 93-110% with an average of 100% and can be said to be satisfactory. In the assessment of Importance Performance Analysis using the Cartesian diagram, 5 attributes were obtained in Quadrant I, which need to be made the main priority of the Abu Saad Gumukmas Clinic, Jember to be improved and 7 attributes were obtained in Quadrant II, which need to be maintained because they are in accordance with patient expectation.